PROSES BERPIKIR KREATIF MATEMATIS SISWA MENURUT DAVID CAMPBELL DITINJAU DARI GAYA KOGNITIF - Dedi Nurjamil; Mumu Mumu; Vepi Apiati; Neni Heryani (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to describe the mathematical creative thinking process of students according to David Campbell's stages in terms of reflective and impulsive cognitive styles on awakening and congruence material. This study used descriptive qualitative research method. Data collection techniques in this study used MFFT (Matching Familiar Figure Test) tests, creative thinking ability tests, and interviews. The main instruments are the researchers themselves and supporting instruments are MFFT (Matching Familiar Figure Test) test instruments and mathematical creative thinking ability test instruments. The subjects of the study were grade IX students of SMPN 1 Tasikmalaya who met all indicators of mathematical creative thinking ability in each cognitive, reflective and impulsive style and could communicate well. The data analysis techniques used are data reduction, data presentation, and conclusions. Based on the results of the study, conclusions were obtained (1) The creative thinking process of reflective students (S1R): can convey information known and asked about questions orally and in writing, show changes in their facial features, do brooding activities while playing stationery, hair and legs slowly, can choose the way of solving obtained after going through the process of guessing smoothly, can show solutions in two ways and Set his own ideas with a long enough time, equate the completion results in the first and second ways and recalculate the completion steps. (2) The creative thinking process of impulsive students (S11I): can understand the problems contained in the problem in a relatively faster time and can mention what is known and asked orally and communicate that what is written has been through calculations outside the head, pay attention to the sketches drawn and be able to write assumptions from the results of their attention, show silent activities and trial and error, can solve in two different ways even if you make a mistake several times, and only equate the final result in both ways and check the steps of the work. (3) The creative thinking process of impulsive students (S25I): can understand the problems in the problem in a relatively faster time, can mention what is known and asked orally, can do trial and error activities and recall ideas found if they have difficulties, do silent activities while playing stationery and veils worn but still look relaxed, can finish in two different ways, as well as simply equate the final result in both ways and check the pace of the work